2010
DOI: 10.1016/j.jconrel.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying of siRNA-containing PLGA nanoparticles intended for inhalation

Abstract: Local delivery of small interfering RNA (siRNA) to the lungs constitutes a promising new area in drug delivery. The present study evaluated parameters of importance for spray drying of siRNA-loaded poly(D,L-lactide-co-glycolide) (PLGA) nanoparticles (NPs) into nanocomposite microparticles intended for inhalation. The spray drying process was optimised using a statistical design of experiment and by evaluating powder characteristics upon systematic variation of the formulation parameters. Concentration, carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 29 publications
3
99
0
3
Order By: Relevance
“…Moreover, studies involving intratracheal delivery of siRNAs show mixed results, likely due to the presence of mucus, mucociliary clearance pathways, and complicated branching structure of the lungs that impair uptake (Lam et al, 2012). Ideally, technology allowing for aerosolization would offer the least-invasive delivery method (Jensen et al, 2010), though these have not yet been reported in clinical settings.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 99%
“…Moreover, studies involving intratracheal delivery of siRNAs show mixed results, likely due to the presence of mucus, mucociliary clearance pathways, and complicated branching structure of the lungs that impair uptake (Lam et al, 2012). Ideally, technology allowing for aerosolization would offer the least-invasive delivery method (Jensen et al, 2010), though these have not yet been reported in clinical settings.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 99%
“…It is interesting to note that lactose is often used as a bulking agent and stabilising adjuvant in spray-dried formulations of sensitive drugs, peptides and proteins to provide some protection during the manufacturing process against shear forces and increased temperatures in particular [200][201][202][203][204][205]. The structure and activity of dried proteins are protected by hydrogen bonding with lactose, which enables the production of stable particles of a size suitable for inhalation and allows a rapid release of the drug in the lung.…”
Section: Use Of Lactose As An "Excipient"mentioning
confidence: 99%
“…After reaching the alveoli, the microparticles were decomposed to nanoparticles, as lactose is soluble in the alveolar lining fluid [205,[212][213][214].…”
Section: Use Of Lactose As An "Excipient"mentioning
confidence: 99%
“…Dry powder aerosol formulation are preferred for macromolecules due to their higher stability during storage, better sterility, easy transportation compared with liquid formulations, and have been successfully used in formulation of other therapeutic macromolecules [23][24][25][26]. To prepare inhalable powder formulations of nucleic acids, either spray drying (SD) or spray freeze drying (SFD) are employed [27][28][29][30]. In the spray drying process, liquids are atomized into sprays which are rapidly evaporated by hot air-stream to give dry particles.…”
Section: Introductionmentioning
confidence: 99%